Evaluation of Cognitive Functions through the Systemic Lisbon Battery: Normative Data - Gamito, P.; Oliveira, J.; Brito, R.; Lopes, P.; Rodelo, L.; Pinto, L.; Morais, D. (Methods of Information in Medicine, 2016)
Introduction: This article is part of the Focus Theme of Methods of Information in Medicine on “Methodologies, Models and Algorithms for Patients Rehabilitation”. Background: ICT is an emerging alternative to paper-and-pencil tests for the assessment of cognitive functions, allowing for the monitoring of participants’ behavior while they perform simulations of instrumental activi -ties of daily life (IADLs) in a virtual reality (VR) scenario. This requires normative values for each VR task, so that deviations to normality can be identified as indicators of cognitive impairment. Objectives: To identify normative data for several IADL tasks that are available on the Systemic Lisbon Battery (SLB). Methods: Fifty-nine participants performed a series of VR tasks that require the use of the memory and executive function dimensions of cognitive functionality. Results: Normative data for the different subsets and total score of the SLB, based on proportion of correct hits per execution time, were identified. Age and experience with video games affect (respectively, negatively and positively) performance on the SLB and should be taken into account in assessment; on the other hand, gender and education do not. Conclusions: Overall results suggest that the SLB may be useful to assess cognitive functioning during the execution of activities of daily living, but larger studies and with clinical samples are needed.
Keywords: Systemic Lisbon Battery; virtual reality; cognitive rehabilitation; normative data